A comprehensive study on parabolic trough solar receiver-reactors of methanol-steam reforming reaction for hydrogen production. (15th April 2019) - Cheng, Ze-Dong; Men, Jing-Jing; Zhao, Xue-Ru; He, Ya-Ling; Tao, Yu-Bing
Highlights: A coupled comprehensive model of parabolic trough solar receiver-reactors is proposed. It is developed with a comprehensive kinetic model, an optical model and a CFD model. Numerical results were compared with reference data and good agreements were obtained. The comprehensive characteristics and performance of different PTSRRs are revealed. The temperature limitation mechanism and optimization with a tradeoff are discussed. Abstract: In this paper, a three-dimensional comprehensive model is firstly proposed for Parabolic Trough Solar Receiver-Reactors (PTSRR) of the Methanol-Steam Reforming Reaction process (MSRR) for hydrogen production. This PTSRR-MSRR comprehensive model is established by combining a comprehensive kinetic model of MSRR, a validated Monte Carlo Ray-Tracing (MCRT) optical model with a Computational Fluid Dynamics (CFD) model based on the Finite Volume Method (FVM), as well as useful comprehensive evaluation indicators. It is capable of comprehensively simulating and evaluating the whole complex photo-thermal-chemical conversion process of the entire PTSRR system, including the concentration, collection and conversion of photon energy, coupled heat transfers, fluid dynamics, multicomponent transports and methanol-steam reforming reactions. After validation, this comprehensive model was successfully used to determine the comprehensive characteristics and performance of different PTSRRs and realistic conditions. The effects and mechanisms of the solar time, the reflector geometric parameters, the inlet methanol molar flow rate, the reaction temperature limitation and the nonuniformity of the concentrated solar flux density distribution were discussed in detail. It is revealed that the reaction temperature limitation that should be smaller than the sintering temperature of Cu/ZnO/Al2 O3 catalyst particles may only appear locally, which is mainly caused by the nonuniformity of the concentrated solar flux density distribution and the corresponding local peak solar flux density. For the mechanism of this kind of temperature limitation, different control strategies and optimizations were examined. Better comprehensive characteristics and performance of PTSRRs can be obtained, by making a reasonable tradeoff between the optical efficiency, the solar flux nonuniformity and the reflector surface curvature characteristics.